Interleukin-1β, but not interleukin-1α, is required for T-cell-dependent antibody production - Nakae, Susumu (Blackwell Science Inc, 2001)
Interleukin-1 (IL-1) consists of two molecules, IL-1α and IL-1β, and IL-1 receptor antagonist (IL-1Ra) is a natural inhibitor of these molecules. Although the adjuvant effects of exogenously administered IL-1 in the humoral immune response are well known, the roles of endogenous IL-1 and the functional discrimination between IL-1α and IL-1β have not been elucidated completely. In this report, we investigated the role of IL-1 in the humoral immune response using gene-targeted mice. Both primary and secondary antibody production against T-dependent antigen, sheep red blood cells (SRBC), was significantly reduced in IL-1α/β(−/−) mice, and was enhanced in IL-1Ra(−/−) mice. The intrinsic functions of B cells, such as antibody production against type 1 T-independent antigen, trinitrophenyl–lipopolysaccharide and proliferative responses against mitogenic stimuli, were normal in IL-1α/β(−/−) mice. The proliferative response of T cells and cytokine production upon stimulation with anti-CD3 monoclonal antibody were also normal, as was the phagocytotic ability of antigen-presenting cells (APCs). However, SRBC-specific proliferative response and cytokine production of T cells through the interaction with APCs were markedly impaired in IL-1α/β(−/−) mice, and enhanced in IL-1Ra(−/−) mice. Moreover, we show that SRBC-specific antibody production was reduced in IL-1β(−/−) mice, but not in IL-1α(−/−) mice. These results show that endogenous IL-1β, but not IL-1α, is involved in T-cell-dependent antibody production, and IL-1 promotes the antigen-specific T-cell helper function through the T-cell–APC interaction.